Kidungan Tradition in Pasunggingan, Pengadegan, Purbalingga - Supriyanto Supriyanto (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
This paper investigates the meaning of Kidungan tradition conducted in Pasunggingan Village, Pengadegan District, Purbalingga. The Kidungan tradition is carried out based on the song composed by Sunan Kalijaga that has contextualization in the community’s life. It is believed that the song aims to get rid of bad luck during the night-time, to be free of all fines and debts, as the prayer to the war, and as the peasantry’s mantra. It is believed that Kidungan tradition has the role as ancestral heritage which has the diversity values. Kidungan tradition becomes an alternative application for salvation, healing, protection and sustenance. The night-time becomes the time chosen to perform Kidungan because it leads a high concentration for praying. The number of song’s functions trusted by the community makes the existence of Kidungan tradition remains until now.